Development of e-wallet application "DASIGU" - based teaching factory - Vrisko Putra Vachruddin; Abdulloh Hamid; Nashudi Nasril (Jurnal Pendidikan Vokasi, 2022)
The trend of non-cash or cashless payments through e-wallet applications is increasing because the application presents the ease of transacting features accompanied by discounts and cashback that are attractive to its users. Not realizing it increases people interest in transacting and shopping both it increases their interest in transacting and shopping online and offline, which will encourage the country's economic growth. So many start-ups and institutions are vying to develop digital wallet applications. Likewise, SMK YPM 3 Taman Sidoarjo is an educational institution based on vocational or expertise to support teaching factory learning and facilitate consumers in transacting it is necessary to develop e-wallet applications in schools. The purpose of this study is to provide an overview of the importance of developing e-wallets in schools aimed at improving the quality of schools through online transactions on products by students. This type of research and development (R&D) with a 4D development model. The stages in this research are defined, designed, developed, and disseminated. The application's assessment instrument uses a Likert scale questionnaire distributed online. A sample was randomly selected from users of the e-wallet application, some teachers and students. The results of the digital wallet application product trial "DASIGU" to 173 students responded with 26 user experience questionnaire indicators resulted in a figure of 73.4% and belonged to the category of "Worth" use. Through the development of this e-wallet application, it will be easier for the school community to transact support products in the form of student services and goods.